Pengaruh Komite Audit, Dewan Komisaris Independen dan Intensitas Modal terhadap Penghindaran Pajak pada Perusahaan Keuangan Yang Terdaftar di BEI Tahun 2015-2019 - Nur Fadilah; Muhaimin Dimyati; Lia Rachmawati (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2022)
This study aims to examine the effect of the audit committee, independent board of commissioners, and capital intensity on tax avoidance as measured by the Cash Effective Tax Rate (CETR). This type of research is quantitative research using secondary data sources. The population used in this study are all financial companies listed on the Indonesia Stock Exchange during 2015 to 2019, namely there are 98 listed financial companies, for determining the research sample using the purposive sampling method so that there are 36 financial companies that match the research criteria made by researcher. Methods of data collection using documentation and literature study. The data analysis technique used in this study is the classical assumption test, multiple linear regression analysis, the coefficient of determination test (R2), hypothesis testing. The results showed that partially independent audit committee and board of commissioners had an effect on tax avoidance, while capital intensity had no effect on tax avoidance. Simultaneously shows that the audit committee, independent board of commissioners, and capital intensity have an effect on tax avoidance.